2019
DOI: 10.1002/cre2.228
|View full text |Cite
|
Sign up to set email alerts
|

CD163+ macrophages infiltration correlates with the immunosuppressive cytokine interleukin 10 expression in tongue leukoplakia

Abstract: ObjectiveAccumulating evidence suggests that macrophages are involved in the immunoediting of oral squamous cell carcinoma but the role of macrophages in oral carcinogenesis is unclear. We aimed to clarify the role of macrophages in oral leukoplakia, which is the most common oral potentially malignant disorder from immunotolerance viewpoint.Materials and methodsThe study included 24 patients who underwent surgical resection for tongue leukoplakia. The relationships between macrophage markers and clinicopatholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 56 publications
1
28
1
Order By: Relevance
“…Several studies have shown that CD163 + macrophages influence the differences in the development of OSCC and the prognoses of patients with OSCC (Fujii et al, ; He et al, ; Troiano et al, ; Usami et al, ; Yamagata et al, ). We recently reported that the infiltration of CD163 + macrophages correlates with the immunosuppressive cytokine interleukin‐10 expression in tongue leukoplakia (TL) (Shigeoka, Koma, Nishio, Komori, & Yokozaki, ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that CD163 + macrophages influence the differences in the development of OSCC and the prognoses of patients with OSCC (Fujii et al, ; He et al, ; Troiano et al, ; Usami et al, ; Yamagata et al, ). We recently reported that the infiltration of CD163 + macrophages correlates with the immunosuppressive cytokine interleukin‐10 expression in tongue leukoplakia (TL) (Shigeoka, Koma, Nishio, Komori, & Yokozaki, ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there is sufficient evidence to support that CD163 is the most important TAM marker of TSCC. We also previously reported the CD163-positive macrophages related to the malignant behavior of oral precancerous lesions (21,22,70). By contrast, reliable human M1 macrophage markers for immunohistochemistry have not been established (6).…”
Section: Discussionmentioning
confidence: 97%
“…Numerous studies have proposed that CD163 is a TAM marker of OSCC ( 14 20 ). We showed in a previous report that subepithelial CD163-positive macrophages are associated with an immunosuppressive cytokine interleukin (IL)-10 secretion in tongue leukoplakia (TL), which is a common OPMD ( 21 ). In addition, we showed that the number of intraepithelial CD163-positive macrophages of TL with invasive carcinoma is remarkably higher than in noninvasive TL, based on immunohistochemical study using human clinical samples ( 22 ).…”
Section: Introductionmentioning
confidence: 97%
“…On the other hand, studies have reported a few rare cases of OVX associated with malignant lesions [36][37][38]. In addition, several investigators have reported about the correlation between CD163 + macrophages and epithelial dysplasia and the malignancy of oral precancerous lesions [13,14,39,40]. Therefore, we must not overlook the malignant potential of squamous epithelium within the OVXs, which are considered as benign reactive lesions.…”
Section: Discussionmentioning
confidence: 97%